The Effect of Rhizoboxes on Plant Growth and Root: Shoot Biomass Partitioning - Mašková, Tereza; Klimeš, Adam (Frontiers in Plant Science, 2020)
Various types of flat rhizoboxes aid in root visualization and tracking in experiments where the focus is upon root system growth and development. While size of the pot is known to affect experiments, nothing is known about the impact of rhizoboxes – not only their volume, but also their shape might affect root and shoot growth. Therefore, we investigated how rhizoboxes change plant biomass and root:shoot biomass partitioning. We compared biomass and root:shoot ratio of plants growing in the pots with different geometry - usual ‘three-dimensional’, cuboid plant pots and flat ‘two-dimensional’ rhizoboxes about the same volume. We used two different nutritional treatments (deionized water and additional nutrients) for investigating whether the nutrient availability in the substrate changed the impact of rhizoboxes on plant growth. We used 15 species for the generalizability of our results across the phylogenetic tree. Proportional investment of plants into roots was similar in usual pots and in rhizoboxes. This pattern was stable across nutrition treatments and across species. Further, we found no differences in total biomass of plants between pot type within nutrient treatments. With added nutrients, the plants had a higher biomass and lower root:shoot ratio compared to treatments without nutrient addition. Thus, species can be safely compared when grown in the rhizoboxes; rhizoboxes did not affect root system growth comparisons among species and nutrient levels. Also, they did not affect plant growth in terms of total biomass.